General Changes as A Condition of Increasing the Efficiency of Public Administration - the Case of The Tax Administration (Vallis Aurea, 2016)
Efficiency has long played a central role in the contested terrain of public administration values. This paper analyzes the existing business processes and explores how to determine the optimal model of business processes in the Tax Administration. The goal of this model of bussines is to increase business efficiency and reflecting on all users of the Tax Administration.